REPRESENTATION OF SHOOTING IN CNN: A CORPUS-BASED CRITICAL DISCOURSE ANALYSIS - Haryono, Aura Hilda; Eliza, Aulia Noor; Faiza, Ema (ETNOLINGUAL, 2025)
Abstract: Nowadays, mass shootings have become a major problem in the United States. The media, especially CNN, plays an important role in shaping ideologies and perceptions of this case. This study aims to analyze CNN's role in representing shooting incidents in the United States from October to November 2023. This research applied a descriptive qualitative method, focusing on corpus-based Critical Discourse Analysis using Fairclough’s (2013) theory. The results found that the collocation and concordance of the word “Shooting” are often associated with verbs and adjectives with negative connotations. Discourse practice analysis indicates CNN’s tendency as a “left-wing” media. Furthermore, socio-cultural practice analysis shows that the shooting incident is related to the international political situation and poor government response. In addition, social factors reflect the ideology, culture, politics, and economic aspects of this shooting case. Thus, CNN’s ideology aligns with the left-wing groups, or liberals, in reporting mass shooting cases in the United States. Keywords: Critical Discourse Analysis (CDA), Corpus, Shooting, CNN